2023
DOI: 10.17755/esosder.1205953
|View full text |Cite
|
Sign up to set email alerts
|

Sinif Öğretmeni̇ Adaylarinin Akademi̇k Moti̇vasyonlarinin Bazi Deği̇şkenler Açisindan İncelenmesi̇

Abstract: Öğretmen adaylarının izledikleri öğrenme süreçlerinde taşıdıkları akademik motivasyon hem mevcut öğrenim süreçleri hem de gelecekte sahip olacakları mesleğin gerekliliklerini yerine getirmeleri adına önem taşımaktadır. Sürdürülen eğitim-öğretim sürecinde hizmet veren öğretim elemanlarının bu anlamda sağladığı katkı ve benimsedikleri sınıf yönetimi yaklaşımları da önemli bir etki oluşturmaktadır. Bu çalışmada, Eğitim Fakültelerinin Temel Eğitim Bölümü, Sınıf Öğretmenliği Anabilim Dalında öğrenim gören öğretmen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
(6 reference statements)
1
2
0
2
Order By: Relevance
“…According to the analysis results, significant negative relationships were found between hopelessness and life satisfaction and self-esteem, and significant positive relationships were found between self-esteem and life satisfaction. These findings are consistent with the literature (Çevik & Yıldız, 2016(Çevik & Yıldız, , Çivilidağ et al, 2018Dikmen ve Şahin Özdemir, 2021;Gençay, 2009;Lyubomirsky et al, 2006;Sarpkaya, 2017). As mentioned before, hopelessness emerges due to the persons negative characterization of current living conditions and negative expectations about the future.…”
Section: Discussionsupporting
confidence: 93%
“…According to the analysis results, significant negative relationships were found between hopelessness and life satisfaction and self-esteem, and significant positive relationships were found between self-esteem and life satisfaction. These findings are consistent with the literature (Çevik & Yıldız, 2016(Çevik & Yıldız, , Çivilidağ et al, 2018Dikmen ve Şahin Özdemir, 2021;Gençay, 2009;Lyubomirsky et al, 2006;Sarpkaya, 2017). As mentioned before, hopelessness emerges due to the persons negative characterization of current living conditions and negative expectations about the future.…”
Section: Discussionsupporting
confidence: 93%
“…It was reported that this situation might be due to not taking a course in classroom management. Contrary to these studies, Yeşilyurt and Çankaya (2008) found in their research with 225 teachers that the classroom management skills of associate degree graduates were higher than those of bachelor's degree graduates. Denizel Güven and Cevher (2005), in their study with 93 preschool teachers, found significant differences in favor of preschool teaching and child development associate degree graduates, and Sadık and Dikici Sığırtmaç (2016) found a significant difference in favor of associate degree graduates between bachelor's and associate degree graduates.…”
Section: Discussion and Resultsmentioning
confidence: 64%
“…Yapılan farklı çalışmada sınıf yönetimi becerilerini uygulamada kadın öğretmenlerin kendilerini daha olumlu ve istekli buldukları ön plana çıkmıştır (Özdemir & Sivrikaya, 2017). Buna karşın yürütülen bir çalışmada ise, erkek öğretmenlerin sınıf yönetimi becerilerinin; esnek davranma, sınıf liderliğini öğrenciye devretme konularında bayan öğretmenlere göre daha üst düzey nitelikte olduğu ön plana çıkmıştır (Yeşilyurt & Çankaya, 2008).…”
Section: Sonuç Tartişma Ve öNeri̇lerunclassified